Using Participatory Research Methods to Foster an Anti-Racist Graduate Learning Environment - Haley Peele; Monica Daniels; Ashlee Yates Flanagan; Stephanie Oshrin; Stacy Overstreet; Chloe Pickett; Andrew Orapallo; Deborah Pickford; Elsia A. Obus (Journal of Participatory Research Methods)
Only within the last few years has the American Psychological Association (APA) acknowledged the impact that the racist history of psychology training, research, and practice has had on people of color (APA, October 2021). As the primary governing organization of psychology, the field looks to the APA to model the possibility of an anti-racist approach to psychology. Training competencies, such as “professionalism,” have persisted as a core foundational skill, yet there is no consensus regarding the definition or essential elements of the competency (Elman et al., 2005; Grus et al., 2018). The lack of clarity in definition and essential elements has left supervising health service psychologists to form more subjective assessments that may be rooted within the field’s racist history. It is therefore unsurprising that professionalism is a concept that has long been weaponized against Black people, Indigenous people, and people of color (BIPOC) in medical and educational settings (Marom, 2019). To address this problem in a School Psychology doctoral program, participatory action research (PAR) methods were utilized to take action towards the creation of an equitable, inclusive, experiential definition of professionalism to reduce opportunities for racist and other discriminatory evaluation. Students and faculty were involved in every phase of the project, from the inception through multiple rounds of analysis and member checking. The result was a programmatic Essence Statement of professionalism, core beliefs about professionalism, and a table of professionalism competencies with definitions and behavioral exemplars, all of which are now codified in the School Psychology Program Handbook and available to all current and prospective students and faculty. The outlined methods can be implemented by professionals across disciplines and systems to actively reduce inequalities in settings where individuals with diverse and intersection identities evaluated by these systems have traditionally been excluded from the processes that impact them.